(untitled) (Bangladesh Journal of Infectious Diseases, 2015)
Background: Early diagnosis of Kala-azar is of prime importance to reduce the transmission of the disease. Objective: The purpose of the present study was to evaluate KAtex test for the diagnosis of Kala-azar. Methodology: This cross sectional study was carried out in Department of Microbiology at Sir Salimullah Medical College, Dhaka for a period of one year from July 2007 to June 2008. Patients were selected clinically form all age and sex group hailing from endemic region of Mymensingh in a semi purposive manner excluding those who have already started taking medicine or refused to participate in the study. Blood and urine samples were collected from the patients admitted in Sir Salimullah Medical College, Dhaka, Mymensingh Medical College and Bhaluka Health Complex, Mymensingh. Result: Among 150 of the clinically selected patients, total 100 cases were confirmed to be positive for Kala-azar by rK39 ICT test. Age and sex matched 25 healthy persons each from endemic and non-endemic area was taken as control. Among the 100 sero-confirmed cases KAtex was positive in 87 (sensitivity of 87%). Among the 50 controls none were positive by KAtex test resulting in specificity of these tests 100% and 98% respectively. Conclusion: KAtex test has high sensitivity and specificity for the diagnosis of Kala-azar patients at endemic region of Bangladesh. Bangladesh J Infect Dis 2014;1(1):8-11